Evaluation of Antibacterial Properties of Citrus amblycarpa (Hassk.) Ochse Peel Extract - Kusumawati, I Gusti Ayu Wita; Yogeswara, Ida Bagus Agung; Wasito, Hendri (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
Limau (Citrus amblycarpa (Hassk.) Ochse) has traditionally been utilized in Balinese medicine for its therapeutic properties. Its peel contains bioactive compounds such as flavonoids, alkaloids, and saponins that have been associated with antioxidant and antibacterial activities. This study aimed to evaluate the antibacterial potential of sequential extracts of C. amblycarpa peel against four pathogenic bacteria. Dried peel powder was sequentially extracted using n-hexane, ethyl acetate, methanol, and water for 72 hours. Each fraction was concentrated with rotary evaporation at 50 °C. The antibacterial activity was assessed by the minimum inhibitory concentration (MIC) method against Escherichia coli, Salmonella typhimurium, Pseudomonas aeruginosa, and Staphylococcus aureus. The results showed that none of the extracts demonstrated inhibitory activity against the tested bacteria. This absence of activity may be related to the loss of volatile antibacterial compounds during the drying process of the plant material. In conclusion, sequential extract of C. amblycarpa peel exhibited no detectable antibacterial effect against common pathogenic bacteria. Despite the negative findings, this study provides baseline data for future investigations, contributes to the scientific understanding of local herbal resources, and emphasizes the importance of optimizing extraction methods to preserve bioactive compound for the development of herbal based antimicrobials.